The Effect of grafting method, number and type of cups on queens production of local hybrid honeybee colonies (Apis mellifera L.) in Lattakia, Syria - مالك عمران,; نور الدين حجيج ,; خليل مكيس,; مينوس اسعد , (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out at the Agricultural Scientific Research Center in Lattakia, during the spring (April) of 2020 it aimed to study the effect of the number of wax and plastic queen bee cell cups, in addition to the method of grafting (wet, dry) on the acceptance rate of grafted larvae and the weight of virgin queens produced from local hybrid bee colonies under the conditions of the Syrian coast. The results showed that the success rate of wet grafting in wax cups when using 16 and 20 queen bee cell cups /colony was 83.33% and 80%, respectively, followed by dry grafting in wax cups with success about (75%), while the success rate of wet grafting in plastic cups was (66.66%). When using 16 cups. As for the weight of the virgin queens, the weights ranged between 0.154 g with dry grafting in plastic cups, and 0.178 g with wet grafting in the wax cups.